Potential of neem oil extract® against Palmetto weevil larvae, Rhynchophorus cruentatus Fabricius (Coleoptera: Curculionidae) and its impact on some detoxification enzymes - B. Gabr; J.M. Lemmons; M.M. El-Bokl (Journal of Entomological and Acarological Research, 2022)
Palmetto weevil, Rhynchophorus cruentatus (Fabricius) (Coleoptera: Curculionidae), is considered the giant weevil in North America (Weissling & Giblin-Davis, 1997). It is a severe pest of palm trees, especially cabbage palms (Sabal palmetto). Larval stages feed heavily on the internal palm soft tissues causing total palm loss (Hunsberger et al., 2000). We know that reports about controlling this pest are very scarce. This research project focuses, for the first time, on controlling Rhynchophorus cruentatus via plant-based insecticides. This study examined the potential of using neem oil extract®, a commercial product, against the third-instar larvae of palmetto weevil (R. cruentatus). Impacts of neem oil extract® on mortality, larval weight, the activity of detoxification enzymes, and thei gene expression levels were examined. Neem oil extract® manifested dose-dependent larvicidal activity against the third-instar larvae of R. cruentatus. Investigations revealed higher mortality and reduction in weight 24 hours post-treatment. LC50 and LC90 values were estimated 24 h post-treatment to be 12.04% and 26.48%, respectively. Biochemical analysis revealed increasing activities of three detoxification enzymes (Acetylcholinesterase, Glutathione S-transferase, and Superoxide dismutase) in the third-instar larvae after 8 h of treatment with LC50. A significant elevation in the expression levels of detoxification genes (Acetylcholinesterase, Glutathione S-transferase, Cytochrome P450, and Superoxide dismutase) was recorded in the treated larva. Our findings help to underline the detoxification mechanisms of R. cruentatus larva against neem oil extract® at both biochemical and molecular levels. Thus, neem oil extract® had a lethal potential against third-instar larvae of R. cruentatus and is suggested as a safe bioinsecticide that may be used in IPM of palm trees as an alternative to chemical insecticides.